(2-x)^3+(2-x)^2*x+4(2-x)=0 , , решить уравнение

Nicalat Nicalat    3   19.08.2019 13:40    0

Ответы
novkristinaa novkristinaa  05.10.2020 05:11
(2-х)³+(2-х)²*х+4(2-х)=0
(2-х)((2-х)²+(2-х)*х+4)=0     вынесли за скобку (2-х)
(2-х)(4-4х+х²+2х-х²+4)=0    раскрыли скобки во второй скобке
(2-х)(8-2х)=0                       привели подобные во второй скобке
2(2-х)(4-х)=0                       вынесли за скобки 2
2-х=0     или    4-х=0
х=2                   х=4
ответ: (2; 4)
ПОКАЗАТЬ ОТВЕТЫ
Frosterion Frosterion  05.10.2020 05:11
(2-х)³+(2-х)²*х+4(2-х)=0
(2-х)((2-х)²+(2-х)*х+4)=0     вынесли за скобку (2-х)
(2-х)(4-4х+х²+2х-х²+4)=0    раскрыли скобки во второй скобке
(2-х)(8-2х)=0                       привели подобные во второй скобке
2(2-х)(4-х)=0                       вынесли за скобки 2
2-х=0     или    4-х=0
х=2                   х=4
ответ: (2; 4)
ПОКАЗАТЬ ОТВЕТЫ